The 2nd International Conference on Sustainable Plantation (ICSP): Improving Added Value of Plantation Crops through Sustainable Plantation. Issue 1 (January 2022) - Syafaruddin,; Sugiyanta,; Wiyono, S; Dirhamsyah, T; Iriani, E S
Abstract : A. SUMMARY OF CONFERENCE 1. Introduction 1.1. Background The Covid-19 pandemic has caused shocks not only in the health aspect but also in all aspects of the global community‟s life. It has significant effect in all sectors of the economy, including the agricultural sector. However, the agricultural sector, including the plantation sub-sector, is a sector that has been able to survive and even shows positive growth. On the other hand, the agricultural commodities from the plantation sector have been significant in job opportunities and export earnings. Major plantation crops such as oil palm, coconut, sago palm, rubber, coffee, cacao, tea, pepper, clove, medicinal plants, and sugarcane may continue their significant contribution to the economy of many tropical countries. These countries will still dominate as the world‟s leading producers of those plantations, at least soon. Plantation and agricultural sectors are labor-intensive. As these sectors are steadily expanding, a reliable workforce requirement has become one of the major issues resulting in huge dependency on capacity development to fulfill the rising need. The 2 nd International Conference on Sustainable Plantation (ICSP) was virtually-held in collaboration between the Faculty of Agriculture, IPB University with Indonesian Center for Estate Crops Research and Development (ICECRD), The Indonesian Agency for Agricultural Research and Development (IAARD), with involving the Indonesian Palmae Crops Research Institute (IPCRI), Indonesian Industrial and Beverage Crops Research Institute (IIBCRI), Indonesian Spice and Medicinal Crops Research Institute (ISMCRI), and Indonesian Sweetener and Fiber Crops Research List of Table, Images, Paper Publication, Funding Acknowledgements, Special Acknowledgements, List Of Committee, Organizing Committee are available in this pdf.